Implementasi Pendidikan Karakter pada Pembelajaran Pendidikan Agama Islam di SMK Al-Mahrusiyah Ngampel Kota Kediri - Farihin, Ahmad (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
This study aims to identify (1) character education planning in PAI learning; (2) implementation of character education in PAI learning; and (3) evaluation of character education in PAI learning. This research is a qualitative research with the type of case study. The research subjects wereprincipals, waka curriculum, teachers, and students. Determination of the subject is done using a purposive technique by selecting a number of respondents who are adjusted to the purpose of this study. Data were collected through observation, in-depth interviews and documentation. The data analysis technique refers to the data analysis steps proposed by Mills and Heberman with an interactive model. The results of the study indicate that (1) in the planning process by compiling teaching modules before carrying out learning activities in the classroom, in which there are learning outcomes, it is hoped that students will be able to understand and realize what they are learning and want to practice it in their daily activities. day; (2) in its implementation by integrating existing character values ​​into all PAI materials; and (3) the evaluation is carried out in two stages, first by means of tests used to determine the extent of cognitive abilities, while the second in non-test evaluations can be assessed from the daily lives of students in participating in learning. Whether the student is active or not during the discussion. This research is expected to contribute to PAI teachers at SMK Al-Mahrusiyah Ngampel Kediri City as an actualization of the internalization of character values ​​through school culture.